Alternative therapies for Covid-19. (2022) - Sundararajan, G.; Isaac, Prince J.; Andal, V.; Lakshmipathy, R.
Abstract: Recently, the outbreak of COVID-19 caused serious global health issues and the world is facing a crisis of antiviral resistance. To overcome the crisis, we reviewed the existing therapies that could be an alternative and effective treatment for COVID-19. Therapies such as ozone, laser, UV radiation and radiation therapy are discussed and the mechanism of killing is elaborated. In conclusion, the ozone, laser and radiation therapy could be considered as an alternative therapy in extirpating the coronavirus from bloodstreams and the challenges in bringing these therapies to clinical trials.